Upaya Peningkatan Pemasaran Melalui Re-Branding UMKM Gula Aren Abang Sabri di Desa Pertumbukan - M. Prahmana Tirta; Yuliana Yuliana; Muhammad Rizki Fadillah; Elvina Zailanty Harahap; Syaiful Amri (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze marketing improvement efforts through a rebranding strategy for the Abang Sabri Palm Sugar MSME in Pertumbukan Village. The background of this study is based on the problem of the suboptimal appeal of local palm sugar products due to simple packaging, a lack of brand identity, and a minimal promotional strategy. The research method used was a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the implementation of rebranding included improvements to packaging design, the creation of a logo and brand identity, and enhancements to digital media-based promotional strategies. These efforts were able to improve product image, expand marketing reach, and increase consumer interest in palm sugar products. Barriers faced included limited capital and knowledge of digital marketing among MSMEs. In conclusion, rebranding is an effective strategy to increase the competitiveness of the Abang Sabri Palm Sugar MSME, but ongoing support and mentoring are needed to achieve optimal results.